Dual Interfacial Modification Engineering for Highly Efficient and Stable Perovskite Solar Cells. Issue 3 (18th January 2021) - Liu, Le; Liu, Dali; Sun, Rui; Zhou, Donglei; Wu, Yanjie; Zhuang, Xinmeng; Liu, Shuainan; Bi, Wenbo; Wang, Nan; Zi, Lu; Zhang, Boxue; Shi, Zhichong; et al.
Abstract : Although the research on perovskite solar cells (PSCs) has achieved rapid progress, its efficiency and stability still need to be further improved to meet the industrial requirements. The defects located inside the cells, on the surfaces, interfaces, or grain boundaries, will primarily affect carrier transportation through the formation of nonradiative recombination centers and hinder the further enhancement of the power conversion efficiency (PCE). Herein, a straightforward and simple defect passivation method is developed to increase the PCE and stability of PSCs. In the device, the N‐type semiconductor AgBiS2 is introduced by thermal evaporation as a modified layer between the perovskite films and electron transport layer, which can improve the charge transport characteristic and bandgap optimization of PSCs. Simultaneously, dimethyl sulfoxide (DMSO) solvent mixed polyethylene glycol (PEG) is used for solvent annealing treatment, which can further improve the quality of perovskite film and reduce the trap density by increasing grain size and enhancing the crystallinity. As a result, the PSCs with dual‐interfacial modification exhibit a remarkable improvement in PCE from 18.58% to 21.19% with exceptional long‐term and moisture stability. This work provides an innovative insight for fabricating the stable and efficient PSCs toward the industrialization. Abstract : In the structure of perovskite solar cells, N‐type semiconductor AgBiS2 and dimethyl sulfoxide solvent mixed polyethylene glycol are used for perovskite film treatment. Finally, the perovskite solar cells with dual‐interfacial modification exhibite a remarkable improvement of power conversion efficiency from 18.58% to 21.19%, as well as show the excellent long‐term and moisture stability.